Resistencia antimicrobiana de bacterias patógenas presentes en el agua del río Chanchán. 2019 - Atiaja Espin, Diana Maribel (2019)
The objective of this study was to evaluate the antimicrobial resistance of pathogenic bacteria present in the Chanchán river water. It is a descriptive, cross-sectional cohort study with a field design. Six different points of the river were selected and three water samples were taken for each sector; data related to water and ambient temperature, pH and height were also obtained. Subsequently, the samples were taken to the Microbiology laboratory of the Faculty of Health Sciences, National University of Chimborazo, where the isolation of infectious bacterial strains was carried out by the sowing and stria technique due to depletion in McConkey culture media, Blood and CLED and were identified by morphological, physiological and biochemical characteristics. The antibiotic resistance profile was determined by the Kirby-Bauer diffusion method interpreted according to the CLSI Clinical and Laboratory Standards Institute. The findings show that Citrobacter diversus, with 41.2% followed by Proteus vulgaris with 29.4%, were the bacteria most frequently at the six points where the samples were collected. Regarding the antimicrobial resistance of the isolated pathogenic bacteria, Proteus mirabilis presented resistance to 6 antibiotics belonging to the families of tetracycline, quinolones, polymyxin, sulfonamides and macrolides and Proteus vulgaris to the families of tetracycline, chilonones and beta-lactams. It is concluded that the presence of these pathogenic bacteria in the Chanchán river represents a public health problem since they can reach the human being through the vegetables that are irrigated with their waters.